Scattering in the Energy Space for Solutions of the Damped Nonlinear Schrödinger Equation on <semantics>Rd×T</semantics> - Taim Saker; Mirko Tarulli; George Venkov (Axioms, 2025)
We will show, in any space dimension <semantics>d≥3</semantics>, the decay and scattering in the energy space for the solution to the damped nonlinear Schrödinger equation posed on <semantics>Rd×T</semantics> and initial data in <semantics>H1(Rd×T)</semantics>. We will also derive new bilinear Morawetz identities and corresponding localized Morawetz estimates.